MODEL KOMUNIKASI DALAM PENGELOLAAN KONFLIK PEMBANGUNAN GEOTERMAL DI KABUPATEN SERANG - Ail Muldi (Jurnal Riset Komunikasi, 2021)
Geothermal conflict in Serang Regency is occured because communication approach is inappropriately done between the company part and local affected community. Geothermal conflict map involves the company geothermal exploration permit holder, regional government, and local community who live in districts around Mount Prakasak Padarincang, becoming a geothermal location. The research was carried out using qualitative method with study case approach. Conflict of geothermal project seen from its characteristic is environmental conflict. Sealed communication of the company made an information gap impact to the creation of different perception with local community about the interest of geothermal construction in Serang regency. Perception gap between both parts underlied the vertical conflict of geothermal environmental came to the peak stage of conflict. Communication between both conflict parts is defensive and confrontational, also tending to violence. Geothermal conflict that nowadays happen surmised will be potential for violence that disserving both parts.